ANALISIS PENGARUH FAKTOR KEUANGAN TERHADAP HARGA SAHAM DI BURSA EFEK JAKARTA - H. Muh. Idrus Stambul (AkMen JURNAL ILMIAH, 2008)
Monetary factor condition, theoretically and empirical have caused share price react negativity or positive, and this is occurence which resulted from systematic risk. The empiric indicate that value of share of company market descend or go up at the time of a monetary factor that is monetary Construct ratio of banking checked to cover capital, assets, earnings and liquidity. The empiric data is consistence with model of signalling theory assuming existence of information asimetri among partisipan in capital market. The model express that market will react negatively caused by finance factors, what indicate existence of various information which do not profit (bad news) about profit condition in the future, specially when happened the finance circumstance which do not profitable.